Exploring the Use of Digital Materials in Teaching Graduate Accounting - Page, James Kyle (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2018)
The use of digital materials in higher education is an integral part of graduate student learning to enhance twenty-first-century skills. Higher education institutions have witnessed an influx of graduate students who prefer the use of digital materials. Digital materials include online assignments, quizzes, and tests. The purpose of this study was to investigate the traditional approach to teaching graduate accounting with textbook only in comparison to teaching with the use of digital materials. The aim was to introduce students to the use of digital materials and how it could be used to enhance their twenty-first-century skills. The primary goal of the study was to determine whether the treatment group learned more than the control group taught in the previous semester the non-traditional approach. The null hypothesis for this study states that there was no difference in student learning outcomes between the group of students who learned using digital materials and students who learned the same course using traditional methods. The mixed-methods study design shed light on the research through the quantitative (cross-sectional) that supported the null hypothesis on the assignment grade section. The results indicate that while there were significant improvements in the overall final grades in the treatment group, the overall final grades of the control group were significantly lower. In conclusion, the use of digital materials alone is not enough to result in enhancing twenty-first-century skills. The study indicated that teaching graduate accounting should include every effective resource at the disposal of the instructor.